THE IMPACT OF SYSTEM QUALITY, INFORMATION QUALITY, SERVICE QUALITY, USE, AND USER SATISFACTION OF SAP INFORMATION SYSTEM ON NET BENEFITS - Wafi Hibatullah SE (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This study aims to test and analyze the impact of system quality, information quality, service quality, use, and user satisfaction of SAP information systems on net benefits. This study adapted the success model of information systems developed by DeLone and McLean (2003). Research is a quantitative study that uses primary data through the distribution of questionnaires. The population in this study were employees of PT Telekomunikasi Indonesia Tbk Operation Finance's Shared Service division which was authorized to use SAP. The study sample consisted of 115 employees. The data analysis too used by researchers is SmartPLS version 2.0 Research results indicate that system quality, information quality, service quality and user satisfaction have a positive effect on net benefits. While use does not effect the net benefits. The results of the study can be used for consideration in determining the policies of what factors need to be improved in the implementation of SAP in the Telkom Office of Bandung City. Keywords: DeLone and McLean, system quality, information quality, service quality, use, user satisfaction, net benefits.